Role of Ambulatory Laparoscopy in Diagnosis of Ascites with Unknown Etiology - Herbert Situmorang; Raymond Surya; Tantri Hellyanti (Indonesian Journal of Obstetrics and Gynecology, 2021)
Background: Ascites could be caused by many underlying diseases, mainly portal hypertension, malignancy, and heart failure. Other etiologies include tuberculosis and pancreatitis. Difficulties in confirming the cause of ascites have been seen in many clinical settings. Ambulatory laparoscopy is one of powerful tools to rule out many etiologies of ascites despite being invasive in its nature. This case report would like to show one case of peritoneal TB presenting with ascites. Patient has undergone many laboratory workups in search of ascites origin. Literature study is done to look for evidence about timing and role of laparoscopy in ascites work-up. Case illustration: A-26-year-old P2 woman came to hospital with a history of vaginal delivery 22 days before admission presenting with massive ascites. No obstetric complication was found. Transvaginal ultrasound revealed normal postpartum uterus and ovaries, surrounded with ascites. Both the liver and kidneys were found normal on ultrasound. Abdominal CT scan with contrast showed massive ascites with thickened omentum. ADA was 36 IU/L. We decided to perform diagnostic laparoscopy and biopsy for histopathology. We found massive yellowish ascites and hyperaemic tubal enlargement with thickening of the peritoneum. Pathology examination proved the appearance of chronic salpingitis and granulomatous peritonitis consistent with tuberculosis peritonitis. Conclusion: Laparoscopy as a minimal invasive tool can diagnose ascites with unknown etiology patients after failure to prove diagnosis from clinical laboratory and radiological examination. It is one best alternative to diagnose peritoneal TB presenting with ascites with its superiority in visualizing abdominal cavity and obtaining specimens for histology with lower risk of morbidity.